2016
DOI: 10.5935/0004-2749.20160023
|View full text |Cite
|
Sign up to set email alerts
|

Short-term visual performance of soft multifocal contact lenses for presbyopia

Abstract: Purpose: To compare visual acuity (VA), contrast sensitivity, stereopsis, and subjective visual performance of Acuvue® Oasys® for Presbyopia (AOP), Air Optix® Aqua Multifocal (AOMF), and Air Optix® Aqua Single Vision (AOSV) lenses in patients with presbyopia. Methods: A single-blinded crossover trial was conducted. Twenty patients with mild presbyopia (add ≤+1.25 D) and 22 with moderate/severe presbyopia (add ≥+1.50 D) who wore lenses bilaterally for 1 h, with a minimum overnight washout period between the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…By the nature of their design, the ACUVUE OASYS for PRESBYOPIA ring design has large abrupt steps with sharp transition zones, which could be responsible for the often reported significant levels of ghosting associated with these lenses. 28 The two steps in the power profiles of the PureVision2 for Presbyopia and Biotrue ONEday for Presbyopia lenses form three distinct power rings, effectively creating a trifocal lens design. The plateaus between the stair-cased reduction of power in the Clariti 1 day lenses are probably too narrow to provide any functional focusing.…”
Section: Discussionmentioning
confidence: 99%
“…By the nature of their design, the ACUVUE OASYS for PRESBYOPIA ring design has large abrupt steps with sharp transition zones, which could be responsible for the often reported significant levels of ghosting associated with these lenses. 28 The two steps in the power profiles of the PureVision2 for Presbyopia and Biotrue ONEday for Presbyopia lenses form three distinct power rings, effectively creating a trifocal lens design. The plateaus between the stair-cased reduction of power in the Clariti 1 day lenses are probably too narrow to provide any functional focusing.…”
Section: Discussionmentioning
confidence: 99%
“…While both objective (Anderson and Stuebing, 2014;Leon et al, 2016) and subjective measures (Cobb, 1964;Donders, 1865;Turner, 1958) of accommodation indicate that to the accommodative response starts to decrease in the early teens, there is only a concurrent drop in accommodative gain by the fifth decade, reducing near image quality and resulting in the apparent acceleration of symptoms in early presbyopes (Almutairi et al, 2017). Presbyopia has even been described as causing the loss of accommodation (Sha et al, 2016).…”
Section: 1mentioning
confidence: 99%
“…MFSCLs are used for correction of presbyopia [27,28] to obtain good vision at all distances. However, some studies [29] suggested that wearing MFSCLs may lead to adverse effects on visual quality and disturbing visual symptoms such as halo and glare, especially at night when the pupils are larger.…”
Section: Introductionmentioning
confidence: 99%